Network Physiology of Exercise: Vision and Perspectives - Balagué, Natàlia; Hristovski, Robert; Almarcha, María del Carmen; Garcia-Retortillo, Sergi; Ivanov, Plamen C. (Frontiers in Physiology, 2020)
The basic theoretical assumptions of Exercise Physiology and its research directions, strongly influenced by reductionism, may hamper the full potential of basic science investigations, and various practical applications to sports performance and exercise as medicine. The aim of this perspective and programmatic article is to: (i) revise the current paradigm of Exercise Physiology and related research on the basis of principles and empirical findings in the new emerging field of Network Physiology and complex systems science; (ii) initiate a new area in Exercise and Sport Science, Network Physiology of Exercise (NPE), with focus on basic laws of interactions and principles of coordination and integration among diverse physiological systems across spatio-temporal scales (from the sub-cellular level to the entire organism), to understand how physiological states and functions emerge from integrated network interactions and to improve the efficacy of exercise in health and sport performance; (iii) to create a forum for developing new research methodologies applicable to the new NPE field, to infer and quantify nonlinear dynamic forms of coupling among diverse systems and stablish basic principles of coordination and network organization of physiological systems. Here we present a programmatic approach for future research directions and potential practical applications. By focusing on research efforts to improve the knowledge about nested dynamics of vertical network interactions, and particularly the horizontal integration of key organ systems during exercise, NPE may enrich Basic Physiology and diverse fields like Exercise and Sports Physiology, Sports Medicine, Sports Rehabilitation, Sport Science or Training Science, and improve the understanding of diverse exercise-related phenomena such as sports performance, fatigue, overtraining, or sport injuries.